Intracranial Bleeding After Reperfusion Therapy in Acute Ischaemic Stroke Patients Randomized to Glyceryl Trinitrate vs. Control: An Individual Patient Data Meta-Analysis - Appleton, Jason P.; Woodhouse, Lisa J.; Sprigg, Nikola; Wardlaw, Joanna M.; Bath, Philip M. (Frontiers in Neurology, 2020)
Background: Thrombolysis, with or without thrombectomy, for acute ischaemic stroke is associated with an increased risk of intracranial bleeding. We assessed whether treatment with glyceryl trinitrate (GTN), a nitric oxide donor, may influence the associated bleeding risk. Methods: We searched for completed randomized controlled trials of GTN vs. no GTN in acute ischaemic stroke with data on reperfusion treatments (thrombolysis and/or thrombectomy). The primary efficacy outcome was functional status as assessed by the modified Rankin Scale (mRS) at day 90; the primary safety outcome was intracranial bleeding. Secondary safety outcomes included symptomatic intracranial hemorrhage and haemorrhagic transformation of infarction. Individual patient data were pooled and meta-analysis performed using ordinal or binary logistic regression with adjustment for trial and prognostic variables both overall and in those randomized within 6 h of symptom onset. Results: Three trials met the eligibility criteria. Of 715 patients with ischaemic stroke who underwent thrombolysis (709, >99%) or thrombectomy (24, 3.4%), 357 (49.9%) received GTN and 358 (50.1%) received no GTN. Overall, there was no difference in the distribution of the mRS at day 90 between GTN vs. no GTN (OR 0.94, 95% CI 0.72–1.23; p = 0.65); similarly, there was no difference in intracranial hemorrhage rates between treatment groups (OR 0.90, 95% CI 0.43–1.89; p = 0.77). In those randomized to GTN vs. no GTN within 6 h of symptom onset, there were numerically fewer bleeding events, but these analyses did not reach statistical significance. Conclusions: In ischaemic stroke patients treated predominantly with thrombolysis, transdermal GTN was safe, but did not influence functional outcome at 90 days.